Peran Manajemen Sumber Daya Manusia dalam Meningkatkan Kesejahteraan Karyawan - Fawaida Ilmalmaula; Rinna Damayanti; Himmatut Taqiyah; Imam Al-Ghazali; Mu’allimin Mu’allimin (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
Employee welfare is a critical issue in the modern business world, where work pressure, burnout, and work-life imbalance can affect productivity and employee retention. This study aims to explore the role of Human Resource Management (HRM) in improving employee welfare through various strategies, including skill development, holistic well-being enhancement, career development, and psychological management. The research method used is a descriptive qualitative literature review, collecting and analyzing data from various sources such as journal articles, books, and research reports. The results indicate that HRM practices such as training, reward systems, and psychological support significantly contribute to enhancing employee welfare. Additionally, effective communication and adaptive leadership also play a crucial role in creating a supportive work environment. This study highlights the importance of a holistic approach and the adaptation of HRM practices according to organizational context and local culture.